Comparison of two graft procedures in a bilateral sinus lift by MRI and histomorphometric analysis: a case report - Maglione Michele; Michelon Filippo; Bevilacqua Lorenzo; Bertolotto Michele; Rothweiler René (Journal of Oral Medicine and Oral Surgery)
Magnetic resonance imaging (MRI) was shown to be a viable method for graft healing evaluation. Platelet-rich fibrin (PRF) was found to speed up bone graft healing process. Sinus lift surgery outcomes after healing period are usually performed with computerized tomography that is not capable to describe graft vascularization and exposes patient to ionizing radiation. The objective of this study is to propose contrast-enhanced magnetic resonance imaging (CE-MRI) as a promising method for the in vivo assessment of sinus lift grafting procedures. A bilateral sinus augmentation surgery was performed. Left sinus was grafted only with bovine deproteinized bone mixed in a 1:1 ratio with autologous bone, in the right sinus, the same biomaterials with the addition of platelet-rich fibrin (PRF) were applied. CE-MRI was performed to evaluate angiogenesis before surgery and at 11, 25, 53, and 104 days after surgery. At 6 months (T0) and after 10 years (T1), before dental implants insertion, bone biopsies were performed and analysed quantitatively. Left sinus graft showed a centripetal pattern of angiogenesis, with the central region remaining unvascularized at 104 days post-surgery. Right side showed a wider and homogeneous vascularization from 25 days after surgery. At T0 new bone formation was only peripheral in the left sinus, whereas it developed both peripherally and through biomaterial in the right sinus. At T1 particles of biomaterial were still present in left sinus, while in right sinus they were not. CE-MRI offers quantitative parameters to evaluate vascularization of biomaterials. The addition of PRF promotes an early development of a widespread vascular system.